2007
DOI: 10.1016/j.psychres.2006.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Combined biological tests for suicide prediction

Abstract: Disturbances in serotonin neuroregulation and in hypothalamic-pituitary-adrenal axis activity are both likely, and possibly independent, factors in the genesis of suicidal behavior. This analysis considers whether clinically accessible measures of these two disturbances have additive value in the estimation of risk for suicide. Seventy-four inpatients with RDC major or schizoaffective depressive disorders entered a prospective follow-up study from 1978-1981, underwent a dexamethasone suppression test (DST) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 44 publications
1
36
1
Order By: Relevance
“…1). Finally, a total of 65 studies met the inclusion criteria and were included in the meta-analysis: 8 cohort studies, 16,[26][27][28][29][30][31][32] 8 case-control studies 13,17,[33][34][35][36][37][38] and 49 cross-sectional studies, 9,10,14,15,18,19, involving 510 392 participants. The participants were categorized as follows: 1) patients with various psychiatric diseases (e.g., depression, schizophrenia, personality disorder, drug and alcohol addictions) with suicidality, who we defined as suicidal patients; 2) patients with various psychiatric diseases without suicidality, who we defined as nonsuicidal patients; and 3) healthy participants without any psychiatric disease and suicidality, who we defined as healthy controls.…”
Section: Search Resultsmentioning
confidence: 99%
“…1). Finally, a total of 65 studies met the inclusion criteria and were included in the meta-analysis: 8 cohort studies, 16,[26][27][28][29][30][31][32] 8 case-control studies 13,17,[33][34][35][36][37][38] and 49 cross-sectional studies, 9,10,14,15,18,19, involving 510 392 participants. The participants were categorized as follows: 1) patients with various psychiatric diseases (e.g., depression, schizophrenia, personality disorder, drug and alcohol addictions) with suicidality, who we defined as suicidal patients; 2) patients with various psychiatric diseases without suicidality, who we defined as nonsuicidal patients; and 3) healthy participants without any psychiatric disease and suicidality, who we defined as healthy controls.…”
Section: Search Resultsmentioning
confidence: 99%
“…Many studies have reported HPA overactivity in relation to suicidality in patients with various psychiatric disorders [9,10,20,26,27] but to our knowledge, little is still known about the connection with stressful life events. Van Heeringen et al [37] compared 17 patients with a history of violent suicidal behaviour with 23 patients without a history of violent suicidal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Maes et al [76] suggested that lower serum HDL levels are probably induced by immune/ inflammatory response in depression. Depression and suicide are associated with low TC and HDL, adiposity and high waist to hip ratio [78][79][80][81][82]. Some studies suggest a relationship between lipid metabolism, serotonin function and poor control of aggressive impulses [78,79,83].…”
Section: Affective Disordersmentioning
confidence: 99%